2011
DOI: 10.1002/hec.1619
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the extra cost of living for people with disabilities

Abstract: Addressing the extra economic costs of disability is a logical step towards alleviating elements of social exclusion for people with disabilities. This paper estimates the long run economic cost of disability in Ireland in terms of the additional spending needs that arise due to disability. It defines and estimates models of the private costs borne by families with individuals who have a disability in Ireland when compared to the wider population, both in general and by severity of disability. Our modelling fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 13 publications
7
68
1
1
Order By: Relevance
“…As noted in Baldwin and Johnson (1994), a blind person might find it difficult to operate a crane but might 8 and Burchardt 2005;Braithwaite and Mont 2009;Cullinan et al 2010). Because disability can both limit and increase household expenditures, the net effect is not a priori obvious.…”
mentioning
confidence: 99%
“…As noted in Baldwin and Johnson (1994), a blind person might find it difficult to operate a crane but might 8 and Burchardt 2005;Braithwaite and Mont 2009;Cullinan et al 2010). Because disability can both limit and increase household expenditures, the net effect is not a priori obvious.…”
mentioning
confidence: 99%
“…The figure is a bit lower than the estimate of 11.5% of household income by Mont and Cuong (2011), yet consistent with estimates from India (Erb & Harriss-White, 2002) and other developing countries (Braithwaite & Mont, 2009). Estimates are significantly lower than those of high-income country settings including the UK (11-69%), Australia (29-37%), Ireland (30-33%; Cullinan et al, 2011;Saunders, 2006;Zaidi & Burchardt, 2003).…”
Section: Discussionmentioning
confidence: 55%
“…Saunders (2006) showed that the extra cost of living with disability in Australia correspond to 29% of 'equivalised income' although this measure increases to 37% when an alternative, and probably more realistic, measure of disability is used (Saunders, 2006). A report by Cullinan et al (2011) estimated the long-run economic cost of disability in Ireland of about 30.3-32.7% of average weekly income.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations